Mineralogical investigations using XRD, XRF, and Raman spectroscopy in a combined approach. (25th April 2018) - Secchi, Maria; Zanatta, Marco; Borovin, Evgeny; Bortolotti, Mauro; Kumar, Arun; Giarola, Marco; Sanson, Andrea; Orberger, Beate; Daldosso, Nicola; Gialanella, Stefano; Mariotto, Gino; Montagna, Maurizio; et al.
Abstract: The identification of mineralogical phases in drill cores is one of the most challenging tasks in the mining activity in view of an efficient metal extraction. This process requires the analytical characterization of large volumes of material to obtain a complete set of data in a minimum of time. None of the commonly used methods in mineralogical analyses, such as IR‐based techniques, X‐rays fluorescence, and hyperspectral imaging, is capable to provide a fully satisfactory response for several reasons, the main one being the complexity of the ores. Moreover, the characterization is often conducted in remote laboratories and only on selected samples to limit the time waste. A possible alternative solution requires a multianalytical approach exploiting on‐field techniques. This strategy is currently being developed within SOLSA, a joint EU H2020 project, and consists of an automatic expert system coupling sonic drilling, imaging, profilometer, hyperspectral cameras, and a combination of Raman spectroscopy, X‐rays fluorescence, and X‐rays diffraction. In this work, the principles on which this cooperative approach is based are discussed, with application to two specific test samples, showing the potential and novelty of the method. In particular, a case is considered in which the sample characterization by the separate use of a single technique fails, whereas the combination of the three analyses (Raman spectroscopy, X‐rays fluorescence, and X‐rays diffraction) works even if the system is very complex. Abstract : In the mining activity, the identification of mineralogical phases in drill cores is one of the most challenging tasks for an efficient metal extraction. A combined approach exploiting Raman spectroscopy, X‐rays fluorescence, and X‐rays diffraction used to identify and quantify mineralogical phases in geological samples is presented. The novelty and the potential of the method are discussed, showing that only a multianalytical characterization gives reliable results in complex systems.